PENINGKATAN KEBERSIHAN GIGI DAN MULUT, PENURUNAN KARIES DAN PENAMBALAN GIGI SISWA MADRASAH IBTIDAIYAH SABILALROSYAD KECAMATAN MARTAPURA BARAT - Nana, Rasuna Ulfah; Said, Fahmi; Rahmawati, Ida (UPPM Poltekkes Kemenkes Banjarmasin, 2023)
The results of the 2018 Basic Health Research National Survey (Riskesdas) reported that the dental health condition of the Indonesian population who experienced dental and oral health problems was 57.6% and only 10% received medical services. This activity aims to increase dental and oral health knowledge and teeth brushing skills, improve dental and oral hygiene, reduce dental caries rates and increase PTI (Performed Treatment Index) numbers. The target of this community service is Sabilalrosyad Ibtidaiyah Madrasah Students, Martapura Barat District, on the banks of the Martapura River, Teluk Selong Village, Martapura Barat District. The implementation of community service activities consists of several stages, namely: the preparation stage, the implementation stage and the evaluation stage. At the implementation stage of the activity carried out dental health counseling, mass tooth brushing assistance, dental examinations, filling of cavities. The results obtained were an increase in knowledge about dental health from medium to high criteria, a decrease in dental caries rates and an increase in the PTI (Performed Treatment Index) rate from 0% to 69%.